2014
DOI: 10.3945/jn.113.190124
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Group Counseling, Cell Phone Messaging, and Participant-Generated Songs and Dramas into a Microcredit Program Increases Nigerian Women’s Adherence to International Breastfeeding Recommendations

Abstract: In northern Nigeria, interventions are urgently needed to narrow the large gap between international breastfeeding recommendations and actual breastfeeding practices. Studies of integrated microcredit and community health interventions documented success in modifying health behaviors but typically had uncontrolled designs. We conducted a cluster-randomized controlled trial in Bauchi State, Nigeria, with the aim of increasing early breastfeeding initiation and exclusive breastfeeding among female microcredit cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
149
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(155 citation statements)
references
References 19 publications
2
149
1
1
Order By: Relevance
“…The survey included questions on knowledge and practices related to breastfeeding and types of food consumed during the previous 24 hours (24), the timing of introduction of fluids and foods (25), and feeding practices in the context of HIV. Women were also asked about the types of IYCF information they received and who had advised them.…”
Section: Methodsmentioning
confidence: 99%
“…The survey included questions on knowledge and practices related to breastfeeding and types of food consumed during the previous 24 hours (24), the timing of introduction of fluids and foods (25), and feeding practices in the context of HIV. Women were also asked about the types of IYCF information they received and who had advised them.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of mHealth interventions in LMICs have targeted HIV/AIDs and family planning/pregnancy, with inconsistent results (Gurman et al, ). Very few mHealth IYCF interventions have been conducted in LMICs to date (Graziose et al, ), and those that have been conducted have primarily focused on exclusive breastfeeding (Flax et al, ; Jiang et al, ; Sellen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that intervention and support by medical professionals [16, 17], family members [18, 19], and peer support groups [20, 21], and use of media technology [22] have helped to boost breastfeeding rates. Employers’ support was also commonly mentioned by working mothers [23, 24].…”
Section: Introductionmentioning
confidence: 99%